Stabilisasi Tanah Lempung Organik Menggunakan Semen Dan Difa Soil Stabilizer - Abdul Halim Muqorrobin; Muhamad Yusa; Ferry Fatnanta (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The bearing capacity of clay soils will decrease by the presence of organic materials in that clay soils. Therefore, the usage of additives such as cement and DIFA SS can be an option to improve the strength of this kind of soil. This research aims to analyze the effects of organic content (varying from 3, 6, 9, and 12% by dry weight) to the CBR values of clay, and to analyze the increase of its strength after stabilized using cement and DIFA SS (5% and 1% by dry weight). The organic clay samples were reconstituted in the laboratory by mixing clay and peat soils. CBR tests were conducted after 0, 7, and 14 days of curing period, and after 4 days for soaked specimens. The results indicate that CBR values of mixing clay decreased significantly from 16,89% to 10,39% due to the addition of 3% organic content. After 14 days, the CBR values of cement-stabilized clay resulted in an increase to 141,04% while the CBR values of clay soils with the addition of cement and DIFA SS improved to 97,17%. Furthermore, the higher the quantity of organic content added to the soils, the lower the CBR values of the stabilized soils. From these results, it is concluded that organic content strongly affects the effectiveness of cement and DIFA SS treatment of the soils. Keywords: CBR, Cement, Clay, DIFA SS, Organic Content, Soil Stabilization